Detection of localized changes in the metabolism of hyperpolarized gluconeogenic precursors 13C‐lactate and 13C‐pyruvate in kidney and liver. Issue 4 (21st April 2016) - von Morze, Cornelius; Chang, Gene‐Yuan; Larson, Peder E.Z.; Shang, Hong; Allu, Prasanna K.R.; Bok, Robert A.; Crane, Jason C.; Olson, Marram P.; Tan, Chou T.; Marco‐Rius, Irene; Nelson, Sarah J.; Kurhanewicz, John; et al.
Abstract : Purpose: The purpose of this study was to characterize tissue‐specific alterations in metabolism of hyperpolarized (HP) gluconeogenic precursors 13 C‐lactate and 13 C‐pyruvate by rat liver and kidneys under conditions of fasting or insulin‐deprived diabetes. Methods: Seven normal rats were studied by MR spectroscopic imaging of both HP 13 C‐lactate and 13 C‐pyruvate in both normal fed and 24 h fasting states, and seven additional rats were scanned after induction of diabetes by streptozotocin (STZ) with insulin withdrawal. Phosphoenolpyruvate carboxykinase (PEPCK) expression levels were also measured in liver and kidney tissues of the STZ‐treated rats. Results: Multiple sets of significant signal modulations were detected, with graded intensity in general between fasting and diabetic states. An approximate two‐fold reduction in the ratio of 13 C‐bicarbonate to total 13 C signal was observed in both organs in fasting. The ratio of HP lactate‐to‐alanine was markedly altered, ranging from a liver‐specific 54% increase in fasting, to increases of 69% and 92% in liver and kidney, respectively, in diabetes. Diabetes resulted in a 40% increase in renal lactate signal. STZ resulted in 5.86‐fold and 2.73‐fold increases in PEPCK expression in liver and kidney, respectively. Conclusion: MRI of HP 13 C gluconeogenic precursors may advance diabetes research by clarifying organ‐specific roles in abnormal diabetic metabolism. Magn Reson Med 77:1429–1437, 2017. © 2016 International Society for Magnetic Resonance in Medicine